Urban sprawl at the expense of cultivated land: decadal land use and land cover changes and future projections in the upper Awash basin of central Ethiopia - Hirpa, Birtukan Abebe; Adane, Girma Berhe; Asrat, Asfawossen; Nedaw, Dessie; Song, Cholho; Roh, Minwoo; Lee, Woo-Kyun (Frontiers in Ecology and Evolution, 2023)
Quantifying land-use and land-cover (LULC) changes is important for sustainable land and ecological management. This study aimed at identifying, classifying and quantifying the changes in LULC during the last two decades (2000–2020) and predict the decadal pattern for the next three decades (2030–2050), with particular emphasis on urban sprawl at the expense of cultivated land in the upper Awash basin of central Ethiopia. Landsat images were used to analyze the LULC change dynamics using hybrid image classification and maximum likelihood classifier techniques. The Cellular Automata-Markov Chain (CAMC) Model was used to predict its future LULC change dynamics. A detailed analysis of the urban sprawl in the cities of Addis Ababa, Adama, and Mojo was also conducted. It was observed that during the last two decades, settlements, particularly urban sprawls, substantially expanded at the expense of cultivated land, whereas the latter modestly expanded at the expense of forestland, bare land, and shrubland. From its size in 2000, the urban sprawl of Addis Ababa has grown in all directions towards cultivated land by more than six times in 2020 and is expected to become double of that by 2050 in the urban and peri-urban areas of the basin. Adama city has expanded by the same rate of 9.7% in the past two decades, while Mojo town has sprawled 9 folds between 2010 and 2020. The predicted percentage change in settlement for Addis Ababa and its neighboring districts within 22 km radius from the centroid shows a 40% expansion in 2030, 77% in 2040, and 87% in 2050 compared with the reference year 2020. Similarly, the Mojo town will expand significantly in 2030 (54%), 2040 (119%), and 2050 (by a staggering magnitude of 244%), while Adama will expand within the 12 km radius by 18%, 42%, and 117% in the next three respective decades. The rapid cultivated land conversions in the basin may contribute to major shifts in urban and peri-urban ecological environments. Our predictive LULC change maps and urban sprawling could be useful for developing effective and sustainable land-use policies for environmental and ecological management in the upper Awash basin.